Cost-effectiveness and readmission rates of laparoscopic vs. open surgery for colorectal cancer: evidence from the health insurance review and assessment service dataset in South Korea - An, Sanghyun; Hong, Sung Eun; Kim, Moo Hyun; Kim, Ik Yong (Frontiers in Surgery, 2025)
IntroductionWe aimed to compare and analyze the cost-effectiveness of laparoscopic vs. open colorectal surgery (CRS) for colorectal cancer using health insurance claims data derived from multiple institutions in South Korea as well as the differences in hospital length of stay (LOS) and 30-day readmission rates related to postoperative complications.MethodsWe retrospectively reviewed the clinical data of patients who underwent curative resection for colorectal cancer between January 1, 2020 and December 31, 2022 using national health insurance claims data in South Korea. We determined the surgical approach based on the presence or absence of treatment material codes specific to laparoscopic surgery, and divided the patients into the laparoscopic-CRS (lap-CRS) and open-CRS groups.ResultsA total of 34,779 patients were included [open-CRS: 3,262 patients [9.4%]; lap-CRS: 31,517 patients [90.6%]]. The mean LOS was 14.11 and 11.27 days for the open- and lap-CRS groups, respectively (p < 0.001). The mean medical costs were 9,163 USD and 8,963 USD in the open- and lap-CRS groups, respectively (p < 0.001). A total of 1,192 (3.4%) patients were readmitted within 30 days of discharge, with a rate of 5.4% (176 cases) and 3.2% (1,016 cases) in the open- and lap-CRS groups, respectively (p < 0.001). Open surgery, male sex, and rectal surgery were identified as factors that increased medical cost.DiscussionAccording to this South Korean nationwide population-based study, laparoscopic surgery demonstrated a reduction in LOS, medical costs, and readmission rates compared with open surgery in patients with colorectal cancer.